A synthetic peptide shows retro- and anterograde neuronal transport before disrupting the chemosensation of plant-pathogenic nematodes. - Dong Wang; Laura M Jones; Peter E Urwin; Howard J Atkinson (PLoS ONE)
Cyst nematodes are a group of plant pathogens each with a defined host range that cause major losses to crops including potato, soybean and sugar beet. The infective mobile stage hatches from dormant eggs and moves a short distance through the soil to plant roots, which it then invades. A novel strategy for control has recently been proposed in which the plant is able to secrete a peptide which disorientates the infective stage and prevents invasion of the pathogen. This study provides indirect evidence to support the mechanism by which one such peptide disrupts chemosensory function in nematodes. The peptide is a disulphide-constrained 7-mer with the amino acid sequence CTTMHPRLC that binds to nicotinic acetylcholine receptors. A fluorescently tagged version of this peptide with both epifluorescent and confocal microscopy was used to demonstrate that retrograde transport occurs from an aqueous environment along bare-ending primary cilia of chemoreceptive sensilla. The peptide is transported to the cell bodies of these neurons and on to a limited number of other neurons to which they connect. It appears to be localised in both neuronal processes and organelles adjacent to nuclei of some neurons suggesting it could be transported through the Golgi apparatus. The peptide takes 2.5 h to reach the neuronal cell bodies. Comparative studies established that similar but less abundant uptake occurs for Caenorhabditis elegans along its well studied dye-filling chemoreceptive neurons. Incubation in peptide solution or root-exudate from transgenic plants that secrete the peptide disrupted normal orientation of infective cyst nematodes to host root diffusate. The peptide probably undergoes transport along the dye-filling non-cholinergic chemoreceptive neurons to their synapses where it is taken up by the interneurons to which they connect. Coordinated responses to chemoreception are disrupted when the sub-set of cholinergic interneurons secrete the peptide at synapses that have post-synaptic nicotinic acetylcholine receptors.